2012
DOI: 10.4161/cc.19901
|View full text |Cite
|
Sign up to set email alerts
|

Wip1 sensitizes p53-negative tumors to apoptosis by regulating the Bax/Bcl-xLratio

Abstract: Wip1 is a stress-response phosphatase that negatively regulates several tumor suppressors, including p53. In a sizeable fraction of tumors, overexpression or amplification of Wip1 compromises p53 functions; inhibition of Wip1 activity is an attractive strategy for improving treatment of these tumors. However, over half of human tumors contain mutations in the p53 gene or have lost both alleles. Recently, we observed that in cancer cells lacking wild-type p53, reduction of Wip1 expression was ineffective, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…The elevation of these cytokine can be linked to the ability of Wip1 to regulate p53 and NF k B pathways. 40,41 These data suggest that Wip1 in immune cells intrinsically controls the sensitivity to DSS-induced colitis through regulation of cytokine production. Yet, the deficiency in Wip1 activity is associated with more severe inflammatory response.…”
Section: Wip1 In Regulation Of Immune Responsementioning
confidence: 83%
“…The elevation of these cytokine can be linked to the ability of Wip1 to regulate p53 and NF k B pathways. 40,41 These data suggest that Wip1 in immune cells intrinsically controls the sensitivity to DSS-induced colitis through regulation of cytokine production. Yet, the deficiency in Wip1 activity is associated with more severe inflammatory response.…”
Section: Wip1 In Regulation Of Immune Responsementioning
confidence: 83%
“…The up-regulation of p53 expression is related to the induction of cell apoptosis by the activity of proapoptotic protein Bax [28]. Caspase-3 has been corroborated as a critical mediator of programmed cell death, and activated caspase plays an important role in the apoptotic response inside the cells [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…13, 15 This activity of Wip1 could underlie the protection of normal cells from the deleterious side effects of anticancer agents. Goloudina et al 21, 22 reported that Wip1 overexpression promotes apoptosis by the Wip1-RUNX2-BAX pathway in p53-negative tumors, but represses apoptosis in p53 wild-type tumors. Activating dephosphorylation of RUNX2 by Wip1 increases its transcriptional activity on the Bax promoter.…”
Section: Discussionmentioning
confidence: 99%
“…19, 20 A recent study reported that Wip1 protects normal cells from hyperactivation during DNA repair activity, thereby reducing toxicity in response to chemotherapeutic agents. 21, 22 The precise role of overexpressed Wip1 in the response to radiotherapy is still unclear. In fact, two opposing responses could be proposed, one involving resistance and the other hypersensitivity to apoptosis in malignant cancers through premature dephosphorylation/inactivation of DNA repair genes or by the total depletion of these signaling responses even before activation.…”
mentioning
confidence: 99%